Conductance of s-Acetylthiocholine Chlorides in Non-Aqueous Solvents at 25 ºC - H. El-Hammamy, Nasr; N. El-Hammamy, Marwa; M. El-Mallah, Nabila; I. Kawana, Aida; M. Moharem, Heba (Asian Journal of Chemistry, 2013)
The conductance of s-acetylthiocholine chlorides has been measured in methanol, ethanol, n-propanol and n-butanol at 25 ºC. The data were analyzed using the Fuoss-Onsager equation for 1:1 associated electrolytes and the characteristic functions, L0 (equivalent conductance at infinite dilution), aº (contact distance of approach) i.e., solvation and KA (association constant) were calculated. The association constant values were analyzed on the basis of the solvent separated-ion pair model. The electrostatic Stokes' radii (R+ + R–) were calculated and their sum was compared with the value of aº confirming the ion pair model. The plot of log KA versus 1/D gave a straight line according to ionic association equation. Zwanzig theory of dielectric friction has been applied to chloride ion in different solvents at 25 ºC. The values of the radius from the slope (hydrated radius) and the intercept (hydrodynamic radius) were examined and the reason for such difference discussed on the basis of the assumptions of Zwanzig theory.